A Case Report On Diagnosis of Malignancy with Serum-Ascites Cholesterol Gradient: LifeScience-Biochemistry - Sumathi, Dr. K.; Nivedhini, Ms. V.P.; Mohamed Rabeek, Dr. Jainulavudeen (International Journal of Life Science and Pharma Research, 2023)
Ascites are the accumulation of fluid in the Abdomen. It happens due to clinical complications from various diseasesthat cause signs and symptoms. Cirrhosis, malignant ascites, and abdominal tuberculosis are the most common causes of ascites.The multiple etiologies of ascites make determining the cause difficult. Several techniques can aid in the differential diagnosis ofascites. However, the techniques are more expensive, invasive, and require more time. As a result, a less expensive and fastermethod of diagnosis, at least as a screening test, would greatly benefit clinicians. Albumin and Cholesterol in serum and ascitic fluidare parameters that would help screen and diagnose cancer. The serum-ascites albumin gradient or gap (SAAG) is a medicalcalculation that helps determine the cause of ascites. In addition, the serum ascites cholesterol gradient (SACG) aids in thedifferential diagnosis.The case study aims to evaluate the significance of serum-ascites cholesterol gradient (SACG) in diagnosingovarian carcinoma. This case report includes a 53-year-old woman who presented to the surgical department with anorexia,indigestion, heartburn, pain or discomfort in the abdominal and pelvic regions, nausea, early satiety, bloating, and weight loss for1 month. She was diagnosed with ovarian carcinoma. The gradients of serum-ascites albumin and serum-ascites Cholesterol werecalculated. Later, the results were compared to Ca-125, an ovarian cancer marker. SAAG showed low sensitivity but high specificityand poor diagnostic performance. Her diagnosis of ovarian carcinoma was confirmed and she was advised to follow up with theoncologist. The current case report will help understand the contribution of the ascitic fluid and serum parameters in a case ofovarian cancer with ascites of unknown etiology.